Peran Pancasila dalam Kehidupan Sehari-Hari pada Generasi Z - Aziz, Mhd Shafwan; Novita, Tri Reni (UNIVERSITAS SERAMBI MEKKAH, 2025)
Pancasila is the ideology of the Indonesian state that contains positive values ​​that must be upheld by society. Pancasila is a guideline for the behavior of good citizens. This study aims to determine the application of Pancasila values ​​among Generation Z who are affected by globalization. Generation Z is an age group that was born and grew up in the digital era, where the development of technology and information affects many aspects of life, including the understanding and practice of national values ​​such as Pancasila.